Numerical Study of a Liquid Droplet Movement in a Microchannel under Laser Heat Source - Huynh, Kim Thach; Le, Thanh Long; Bui, Trong Hieu (Old Journal, 2019)
In this study, the numerical methods are used to simulate the liquid droplet migration in a microchannel. A 40 mW heat source is placed at the distance of 1 mm from the initial position of a water droplet. To determine the exact position of a liquid droplet in a microchannel and clearly observe the surface tension of a droplet during the actuation process, we employed the finite element method with the two-phase level set technique. Both the upper wall and the bottom wall of the microchannel are set to be an ambient temperature. When the heat source is turned on, a pair of asymmetric thermocapillary convection vortices is formed inside the droplet. The thermocapillary force caused by the temperature gradient inside the droplet and the capillary force caused by the pressure gradient drive the droplet to move in a microchannel. The numerical results show the temperature gradient inside a microchannel due to laser heat source affects the behavior of a droplet movement. The actuation velocity of the water droplet increases significantly, and then decreases continuously. The dynamic contact angle is strongly affected by the oil flow motion and the thermo capillary momentum inside the droplet. The advancing contact angle is larger than the receding contact angle during the actuation process.